2023
DOI: 10.1002/ece3.10336
|View full text |Cite
|
Sign up to set email alerts
|

Hogs sleep like logs: Wild boars reduce the risk of anthropic disturbance by adjusting where they rest

Abstract: Resting is a crucial daily requirement for all animals. It serves various purposes such as energy conservation (Glass et al., 2021;Riede et al., 2017), thermoregulation (Lutermann et al., 2010, and predator avoidance (Lima et al., 2005). Additionally, rest encompasses sleep, which is essential for neuro-physiological homeostasis (Freiberg, 2020;Schmidt, 2014). To meet physiological requirements and integrate ecological constraints, such as predation risk, animals allocate a significant proportion-often more th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Boars are known to change their behaviour to avoid anthropogenic disturbances – in our case manually opened carcasses (e.g. Fradin & Chamaillé‐Jammes, 2023 ; Johann et al., 2020 ). Moreover, wild boar is extremely sensitive to olfactory cues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Boars are known to change their behaviour to avoid anthropogenic disturbances – in our case manually opened carcasses (e.g. Fradin & Chamaillé‐Jammes, 2023 ; Johann et al., 2020 ). Moreover, wild boar is extremely sensitive to olfactory cues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As animals are more difficult to detect by humans at night, they may not feel the need to move as far after a disturbance. Fradin and Chamaillé‐Jammes (2023) also showed that wild boar exhibit limited daytime movement, even in highly human‐dominated landscapes, but when they do move, possibly due to human disturbance, their distances are typically short (<500 m), except when they are actively hunted. During our experimental approaches, we did not observe any aggressive reactions from wild boar towards the observers, who were only observed or heard on two occasions (out of 29 trials).…”
Section: Discussionmentioning
confidence: 99%
“…This observation reinforces the tendency of wild boar to avoid humans. On a fine scale, wild boar may rely on vegetation for hiding or escape (Marini et al., 2008; Fradin & Chamaillé‐Jammes, 2023; personal observation) and on a landscape scale, wild boar may avoid human structures during the day when human activity is the highest (Ohashi et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations